Inventory Management and Endogenous Demand: Investigating the Role of Customer Referrals, Defections, and Product Market Failure. (28th June 2018) - Sokolinskiy, Oleg; Sopranzetti, Ben; Rogers, Dale S.; Leuschner, Rudolf
ABSTRACT: This article optimizes a finite population, dynamic, stochastic inventory model where future demand is endogenous to inventory policy. Specifically, satisfied customers are not only likely to remain with the firm, but may also refer new customers. In contrast, backorders and lost sales may cause disgruntled customers to defect and potentially cause them to dissuade new customers from doing business with the firm. Thus, inventory policy and customer demand are endogenous. Further, the model allows for the possibility that too many customer defections may lead to product market failure. The incorporation of these innovations into our model yields inventory policies that differ substantially from those reported in the literature, with the greatest differences occurring when the firm has low to medium market share.